THE MEANING ANALYSIS OF “TO DIANEME” IN ROBERT HERRICK'S POEM (Semiotic Approach in Literature Analysis) - Ayu Bandu Retnomurti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2013)
In this research study, the writer would like to describe “The Meaning Analysis of “To Dianeme” in Robert Herrick's Poem (Semiotic Approach in Literature Analysis)”. Descriptive qualitative method is used by the writer for the study and also received most of the source from the internet for the related subject as references. The finding of this poem there are two meaning which can be found in “To Dianeme” such as heuristic like denotative meaning and hermeneutic like connotative meaning. As the main source of data consists of one short story which entitled “To Dianeme” in Robert Herrick's Poem and the secondary data used from reference books and internet.Keywords: Meaning, Semiotic, Literature, Heuristic, Hermeneutic.